2016
DOI: 10.1111/medu.13069
|View full text |Cite
|
Sign up to set email alerts
|

Test-enhanced learning of clinical reasoning: a crossover randomised trial

Abstract: This is the first study to demonstrate an effect of test-enhanced learning on clinical reasoning as assessed with key feature questions. In this randomised trial, repeated testing was more effective than repeated case-based learning alone. Curricular implementation of longitudinal key feature testing may considerably enhance student learning outcomes in relevant aspects of clinical medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
46
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 30 publications
2
46
0
2
Order By: Relevance
“…Increased exposure to the material to be learnt may by itself increase learning outcome. In addition, current research on the impact of repeated testing on long-term retention 35 suggests that the additional testing that occurred in the intervention group may have further increased learning outcome in the intervention group. We are unable to differentiate whether the improvement in outcomes occurred due to these specific interventions themselves or additional exposure time in the intervention group.…”
Section: Discussionmentioning
confidence: 99%
“…Increased exposure to the material to be learnt may by itself increase learning outcome. In addition, current research on the impact of repeated testing on long-term retention 35 suggests that the additional testing that occurred in the intervention group may have further increased learning outcome in the intervention group. We are unable to differentiate whether the improvement in outcomes occurred due to these specific interventions themselves or additional exposure time in the intervention group.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of Raupach et al . support the pure and post‐assessment effects of key feature problems on clinical reasoning.…”
mentioning
confidence: 72%
“…This meant at the time Year 1 students completed the test for this study, they had only completed two practical anatomy examinations (spot tests) but had not taken a final written examination on MSKanat. The process of testing (Logan et al, ; Dobson and Linderholm, ; McNulty et al, ; Raupach et al, ; Kleinberg et al, ), and retrieval of knowledge that occurs during testing, has been shown to increase retention (Karpicke and Roediger, ; Karpicke, ; Smith et al, ) and the lead up to final examinations usually involves large amounts of dedicated study by students to review and consolidate their knowledge prior to being examined on it. As such, data collection prior to their first theory examination on this anatomy may have negatively influenced results from Year 1, and if tested a few weeks later may have had higher results.…”
Section: Discussionmentioning
confidence: 99%
“…If vertical integration is regarded as a solution to reduced teaching time for anatomy learning in the early years of a program, with anatomy curricula divided, rather than revisited and applied, across the program, then the benefits of increasing the depth of knowledge will not be achieved. Repetition, retrieval (Parmar and Rathinam, ; Karpicke and Blunt, ; Karpicke, ; Lehman and Karpicke, ), and testing (Logan et al, ; Dobson and Linderholm, ; Raupach et al, ) are highly regarded as major contributors to retaining and developing knowledge.…”
Section: Discussionmentioning
confidence: 99%